Sialic acid‐dependent interaction of group B streptococci with influenza virus‐infected cells reveals a novel adherence and invasion mechanism. (16th January 2018) - Tong, Jie; Fu, Yuguang; Wu, Nai‐Huei; Rohde, Manfred; Meng, Fandan; Valentin‐Weigand, Peter; Herrler, Georg
Abstract: Group B streptococci (GBS) contain a capsular polysaccharide with side chains terminating in α2, 3‐linked sialic acids. Because of this linkage type, the sialic acids of GBS are recognised by lectins of immune cells. This interaction results in a dampening of the host immune response and thus promotes immune evasion. As several influenza A viruses (IAV) use α2, 3‐linked sialic acid as a receptor determinant for binding to host cells, we analysed whether GBS and influenza viruses can interact with each other and how this interaction affects viral replication and bacterial adherence to and invasion of host cells. A co‐sedimentation assay revealed that viruses with a preference for α2, 3‐linked sialic acids bind to GBS in a sialic acid‐dependent manner. There is, however, a large variation in the efficiency of binding among avian influenza viruses of different subtypes as shown by a hemagglutination‐inhibition assay. A delay in the growth curve of IAV indicated that GBS has an inhibitory effect on virus replication. On the other hand, both the adherence and invasion efficiency of GBS were enhanced when the cells were pre‐infected by IAV with appropriate receptor specificity. Our results suggest that GBS infection may result in a more severe disease when patients are co‐infected by influenza viruses. This co‐infection mechanism may have relevance also to other human diseases, as there are more bacterial pathogens with α2, 3‐linked sialic acids and human viruses binding to this linkage type.